PPP1R15A-mediated dephosphorylation of eIF2α is unaffected by Sephin1 or Guanabenz - Crespillo-Casado, Ana; Chambers, Joseph E.; Fischer, Peter M.; Marciniak, Stefan J.; Ron, David (eLife Sciences Publications, 2017)
Dephosphorylation of translation initiation factor 2 (eIF2α) terminates signalling in the mammalian integrated stress response (ISR) and has emerged as a promising target for modifying the course of protein misfolding diseases. The [(o-chlorobenzylidene)amino]guanidines (Guanabenz and Sephin1) have been proposed to exert protective effects against misfolding by interfering with eIF2α-P dephosphorylation through selective disruption of a PP1-PPP1R15A holophosphatase complex. Surprisingly, they proved inert in vitro affecting neither stability of the PP1-PPP1R15A complex nor substrate-specific dephosphorylation. Furthermore, eIF2α-P dephosphorylation, assessed by a kinase shut-off experiment, progressed normally in Sephin1-treated cells. Consistent with its role in defending proteostasis, Sephin1 attenuated the IRE1 branch of the endoplasmic reticulum unfolded protein response. However, repression was noted in both wildtype and Ppp1r15a deleted cells and in cells rendered ISR-deficient by CRISPR editing of the Eif2s1 locus to encode a non-phosphorylatable eIF2α (eIF2αS51A). These findings challenge the view that [(o-chlorobenzylidene)amino]guanidines restore proteostasis by interfering with eIF2α-P dephosphorylation.